Alternative sources of antigenic peptides for self and non-self recognition. (October 2022) - Sroka, Ewa Maria; Martins, Rodrigo Prado; Daskalogianni, Chrysoula; Malbert-Colas, Laurence; Lavigne, Mathilde; Apcher, Sebastien; Fahraeus, Robin
Abstract : MHC class I presentation pathway plays a crucial role in the immune system and allows to distinguish self from non-self. In the thymus, developing thymocytes undergo positive and negative selection once exposed to self-peptide:MHC complexes on cortical (cTECs) and medullar (mTECs) thymic epithelial cells as well as some antigen presenting cells (e.g. macrophages and dendritic cells). In the result of this process the immune system is capable of recognizing and responding to foreign peptides presented on self-MHC molecules. Discoveries of alternative sources of antigenic peptides (e.g. DRIPs and PTPs) challenged the notion about full-length proteins being the main supplier of material for the MHC class I pathway and shifted a focus of search for new sources to ribosomal scanning during pioneer round of translation. Works related to Epstein-Barr virus has shown that MHC class I immune surveillance is directly correlated with the mechanism that regulates protein synthesis. Together with other recent results it highlights the importance of pre-mRNA and mRNA processing in providing antigenic peptides for MHC class I surveillance. The lack of animal models to study the origin of alternative antigenic peptides hinders research in the field of neoantigens. I will describe results of the presentation of intron-derived antigenic peptides in mice model developed by our team. We will also revise some significant research related to the production of alternative antigenic peptides, their importance in cancer research, immunosurveillance and generation of tolerance.